Human–Computer Interaction (2000–2026): Scopus-Based Bibliometric Mapping of Core Topics and Methodological Trends - Loso Judijanto (West Science Information System and Technology, 2026)
In this paper, bibliometric methods have been applied to analyze the development and knowledge structures of Human–Computer Interaction (HCI) from 2000 to 2026. The Scopus database was used for data acquisition and VOSviewer software was employed for visualizing research collaboration patterns, identifying prominent papers, and examining keyword trends in HCI research. Co-authorship, citation, and keywords co-occurrences were applied for analyzing the development of HCI. Results indicated that over time, the main focus of HCI research changed from usability and user interface issues to more advanced topics like integration of artificial intelligence technologies, deep learning, and domain-specific applications such as health-care sciences. Regarding collaboration among researchers in HCI, results depicted strong clusters of research inside this field with some connections to the outside world. Furthermore, the main reason for the high number of citations was the use of methodological tools that could be applied in all other fields and were considered generalizable. Overall, the findings of this study indicated the increasing trend towards developing an intelligent and adaptive HCI system based on machine learning.